Gaucher Disease and Dental Approaches - Aşantoğrol, Firdevs; Dursun, Hüseyin; Canger, Emin Murat; Bayram, Fahri (European Journal of Therapeutics, 2023)
Gaucher disease (GD) is a lysosomal storage disease that results in glucocerebroside accumulation in the lysosomes due to deficiency of the enzyme glucocerebrosidase (GBA). GD, inherited as an autosomal recessive disorder, is a panethnic disease. However, it is most common in Ashkenazi Jews with a rate of 1/13. GD typically presents organomegaly and multiple organ involvement, in which the bone marrow is infiltrated by lipid-laden macrophages. Three clinical types have been identified based on whether neurological involvement of GD is observed. Type I GD is non-neuronopathic and the most common clinical type. The diagnosis of GD is determined by detecting low levels of GBA enzyme in peripheral blood leukocytes. Mutation analysis should be performed in patients with low enzyme levels. Specific treatment of GD includes enzyme replacement therapy (ERT) as a first step and substrate reduction therapy that can be tried in patients who cannot tolerate ERT. Bisphosphonates can be used as supportive therapy in patients with osteoporosis when there is no response to specific therapy. It is extremely important for dentists to be familiar with the maxillofacial abnormalities such as generalized osteopenia, enlarged bone marrow spaces, pseudocystic lesions, cortical thinning, and mental demineralization observed in the patients with GD, as well as multiple organ involvement, and hematological and skeletal involvement of GD. The aim of this review is to comprehensively point out the general involvement of GD and to illuminate the dentomaxillofacial findings of this disease, leading dentists on possible oral and dental complications that may develop in dental and surgical procedures of the patients with GD.